(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
This ongoing research aims to analyze the technical and ethical procedures adopted by the electronic journals of the Federal University of Alagoas (UFAL) with Qualis classification, according to CAPES evaluation. The investigation seeks to understand whether the editorial practices of these journals are based on transparency and ethical conduct, addressing criteria such as submission, review, and publication of scientific works. The research also explores the relevance of Open Science and its impact on scientific communication, proposing improvements to editorial policies with a focus on process optimization. The adopted methodology is qualitative and exploratory, based on a document analysis of the journals available on the UFAL Journals Portal.